Group 3 Pulmonary Hypertension: From Bench to Bedside. Issue 9 (29th April 2022) - Singh, Navneet; Dorfmüller, Peter; Shlobin, Oksana A.; Ventetuolo, Corey E.
Abstract : Pulmonary hypertension (PH) because of chronic lung disease is categorized as Group 3 PH in the most recent classification system. Prevalence of these diseases is increasing over time, creating a growing need for effective therapeutic options. Recent approval of the first pulmonary arterial hypertension therapy for the treatment of Group 3 PH related to interstitial lung disease represents an encouraging advancement. This review focuses on molecular mechanisms contributing to pulmonary vasculopathy in chronic hypoxia, the pathology and epidemiology of Group 3 PH, the right ventricular dysfunction observed in this population and clinical trial data that inform the use of pulmonary vasodilators in Group 3 PH.